Web-Based Financial Management System for HKBP Cimahi Church, Sisingamangaraja Street: Sistem Keuangan Gereja HKBP Cimahi Jalan Sisingamangaraja Berbasis Website - Pardede, Jasman; Premitasari, Marisa; Perdinan, Rivan Dio; Al Fauzan, Farel Anugrah; Supriyandari, Listy Nuri; Sandia, Muhammad Sakha; Ramdani, Dadan (Institut Riset dan Publikasi Indonesia, 2026)
transaction tracking, and limited financial transparency. This community service program (PKM) addresses the question of how a website-based financial system can improve the efficiency and transparency of financial management at HKBP Cimahi Sisingamangaraja Church. The position of this activity lies in the implementation and development of a church financial management system as a technological solution to existing administrative challenges. The system was developed using the waterfall method, which includes requirement analysis, system design and implementation, as well as testing and evaluation stages. The results of the implementation indicate that the website-based financial system is capable of centralizing financial data management, simplifying transaction recording processes, and enhancing the transparency of church financial management. These findings demonstrate that the adoption of a web-based financial system can effectively support more accountable and efficient financial administration within church organizations.